The Relationship between Oil Prices and Real Estate Loans and Mortgage Loans in Azerbaijan - Humbatova, Sugra Ingilab; Hajiyev, Natig Gadim-Ogli (International Journal of Energy Economics and Policy, 2020)
Azerbaijan is a major exporter of natural resources (oil). Improving the welfare of the population is a priority, as the driving force of the modern economy, including future economic progress, is the human factor, human capital, its science, knowledge, ability to use technology. Thus, at the current stage of Azerbaijan's economic development, the issue of social welfare, including housing, is one of the most important indicators of the sustainability of dynamic socio-economic development in the country in the long run. For this reason, the study of the issue of directing part of the oil capital to mortgage loans and real estate is urgent.Taking into account the dependence of oil revenues on world oil prices, the article examines the relationship between world oil prices in the Republic of Azerbaijan over the past 10 years (2010M01âˆ’2020M01) between mortgage loans and real estate loans. The ARDL model was used as a research model. In addition, stationary tests of variables (ADF, PP, KPSS) were performed and the Engle-Granger cointegration equation was evaluated using both FMOLS and DOLS, as well as CCR. The stability of the models was studied. EViews_9 econometric software was used for calculations and graphing.As a result of the analysis, it was theoretically determined that there is a certain positive correlation between world oil prices, mortgage loans and real estate loans. Our recommendation may be to accelerate the transfer of part of oil revenues to mortgage loans and real estate to improve housing. Keywords: oil revenues, oil prices, mortgages and real estate loans, housing market, ARDL. JEL Classifications: E50, I39, P28, Q43, R21, R38 DOI: https://doi.org/10.32479/ijeep.10532